2016
DOI: 10.1097/01.jaa.0000473374.55372.8f
|View full text |Cite
|
Sign up to set email alerts
|

Managing acute invasive fungal sinusitis

Abstract: Acute invasive fungal sinusitis is the most aggressive form of fungal sinusitis and can be fatal, especially in patients who are immunosuppressed. Early diagnosis and intervention are crucial and potentially lifesaving, so primary care providers must maintain a high index of suspicion for this disease. Patients may need to be admitted to the hospital for IV antifungal therapy and surgical debridement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(22 reference statements)
0
10
0
5
Order By: Relevance
“…Imaging workup is essential to evaluate extra-sinonasal extensiveness of the disease and for surgical planning. CT scans and MRI are necessary to evaluate bone and soft tissue involvements (i.e., orbit/brain), respectively [2, 8], although their findings in early stages are usually non-specific [7]. Unilateral disease and bone thickening on CT scans are highly suggestive of AIFRS [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging workup is essential to evaluate extra-sinonasal extensiveness of the disease and for surgical planning. CT scans and MRI are necessary to evaluate bone and soft tissue involvements (i.e., orbit/brain), respectively [2, 8], although their findings in early stages are usually non-specific [7]. Unilateral disease and bone thickening on CT scans are highly suggestive of AIFRS [6].…”
Section: Introductionmentioning
confidence: 99%
“…Formalin-fixed paraffin-embedded (FFPE) histopathological exam, including hematoxylin-eosin (HE) and Gomori methenamine-silver (GMS) staining, is the most reliable test to confirm fungi invasion into the tissue [3, 8, 9]. However, processing for FFPE is time-consuming, which contrasts with the urgency to diagnose AIFRS.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al[24] studied 46 patients with invasive fungal sinusitis and suggested that early introduction of an anti-fungal agent and aggressive surgical debridement potentially decrease morbidity and mortality in high-risk patients. Other accompanying treatments should include tight regulation of blood glucose, management of diabetic ketoacidosis, and reversal of the underlying immunocompromised state when possible[25].…”
Section: Discussionmentioning
confidence: 99%
“…Schwartz et al[27] studied 54 consecutive patients with acute myelogenous leukemia and reported that major factors associated with cases ultimately developing IFD included the duration of chemotherapy, the number of sites colonized with fungi, and the number of fungal species isolated on certain surveillance cultures. According to the study of Dwyhalo et al[25], patients who are diagnosed and treated early, i.e ., when the fungal load is low, have the best outcomes. In our case, the patient’s condition gradually stabilized after surgical debridement and antifungal drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy regarding the best methods for the prevention, diagnosis and treatment of IFS. Early diagnosis and intervention are critical and could be lifesaving (4). The identification of species of the fungi is a key to anti-fungal therapy and also surgical intervention.…”
Section: Introductionmentioning
confidence: 99%